Teaching Critical Discourse Analysis to ELT Learners through Corpus Based Approach - samsi, yogi setia (Universitas Swadaya Gunung Jati, 2019)
ABSTRACTConcordance is the software that facilitates an unlimited data recognizing the frequency and collocation. It can be used for learning and teaching. This study is qualitative and aimed to know the contribution of corpus tool in teaching CDA and the students’ responses through the use of corpus tool, named concordance software, in one of the University. The method in this research is qualitative descriptive with the content analysis. Thus, I employed the frequency and collocation in order to get its sociocognitive contained into three levels of analysis: microstructure, superstructure, and macrostructure couched within critical discourse analysis framework of Van Dijk (2008) through 2 articles taken from different newspaper that has been collected into concordance software. The data can be represented to be mediator in learning and teaching CDA in the class to find out the ideology through frequency and collocation. The findings reveal that concordance has the contribution to the learning and teaching especially in linguistic course. It is questioningly proven by the students’ responses that the students seemingly motivate and enthuse to learn CDA through corpus linguistics. Concordance is effective and can help the teacher in their teaching.